Is it Arrogant to Deny Climate Change or is it Arrogant to Say it is Arrogant? Understanding Arrogance and Cultivating Humility in Climate Change Discourse and Education. (December 2015) - Ferkany, Matt
This paper assesses the charge that climate change denial is arrogant and considers the educational priorities most appropriate to fostering greater humility about the climate change problem. I argue that even denial formed in ignorance of the organised misinformation campaign often constitutes a kind of arrogance, but that it is quite possible to humbly doubt the climate change problem. In some cases denial flows from other more or less serious errors or vices, such as ignorance, sincere but mistaken belief, dishonesty or selfishness. Those who press the arrogance charge also risk being arrogant in doing so. Educators can do a number of things to promote greater humility about climate change, including providing experiences that increase people's appreciation of their individual and general human limitations and improving their ability to distinguish credible from discreditable sources of scientific information and factual from normative dimensions of the climate change problem.